HTLV in the Americas: challenges and perspectives El virus de la leucemia humana de células T (VLHT) en las Américas: retos y perspectivas - Anna Bárbara F. Carneiro-Proietti; Bernadette C. Catalan-Soares; Carlos M. Castro-Costa; Edward L. Murphy; Ester C. Sabino; Michie Hisada; Bernardo Galvão-Castro; Luiz C. J. Alcantara; Carlo Remondegui; Kristien Verdonck; Fernando A. Proietti (Pan American Health Organization, 2006)
The first description of the human T-lymphotropic virus type 1 (HTLV-1) was made in 1980, followed closely by the discovery of HTLV-2, in 1982. Since then, the main characteristics of these viruses, commonly referred to as HTLV-1/2, have been thoroughly studied. Central and South America and the Caribbean are areas of high prevalence of HTLV-1 and HTVL-2 and have clusters of infected people. The major modes of transmission have been through sexual contact, blood, and mother to child via breast-feeding. HTLV-1 is associated with adult T-cell leukemia/lymphoma (ATL), HTLV-associated myelopathy/tropical spastic paraparesis (HAM/ TSP), and HTLV-associated uveitis as well as infectious dermatitis of children. More clarification is needed in the possible role of HTLV in rheumatologic, psychiatric, and infectious diseases. Since cures for ATL and HAM/TSP are lacking and no vaccine is available to prevent HTLV-1 and HTLV-2 transmission, these illnesses impose enormous social and financial costs on infected individuals, their families, and health care systems. For this reason, public health interventions aimed at counseling and educating high-risk individuals and populations are of vital importance. In the Americas this is especially important in the areas of high prevalence. La primera descripción del virus de la leucemia humana de células T tipo 1 (VLHT-1) se hizo en 1980, y al poco tiempo, en 1982, se descubrió el VLHT-2. Desde entonces las características principales de estos virus, a los que a menudo se les llama VLHT-1/2, se han estudiado exhaustivamente. Centroamérica, América del Sur y el Caribe son áreas con una alta prevalencia de VLHT-1 y VLHT-2 donde hay conglomerados de personas infectadas. Las principales vías de transmisión han sido el contacto sexual, la sangre y sus derivados, y la de madre a hijo por la leche materna. El VLHT-1 se asocia con la leucemia o el linfoma de células T maduras (LTM), la mielopatía o paraparesia tropical espástica ligada al VLHT (M/PTE), y la uveítis ligada al VLHT, así como ...